2020
DOI: 10.1186/s12974-020-1717-8
|View full text |Cite
|
Sign up to set email alerts
|

Immune network dysregulation associated with child neurodevelopmental delay: modulatory role of prenatal alcohol exposure

Abstract: Background: Evidence suggests that cytokine imbalances may be at the root of deficits that occur in numerous neurodevelopmental disorders, including schizophrenia and autism spectrum disorder. Notably, while clinical studies have demonstrated maternal cytokine imbalances with alcohol consumption during pregnancy-and data from animal models have identified immune disturbances in alcohol-exposed offspring-to date, immune alterations in alcohol-exposed children have not been explored. Thus, here we hypothesized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 93 publications
2
29
0
1
Order By: Relevance
“…Moreover, sex differences in PAE-linked cytokine expression, and the suppression of splenic Tregs, may elevate the risk for autoimmune disorders and explain variations in FASD-associated behaviors. These data are consistent with a number of previous studies that link immune system dysfunction to neuropathy and to adverse behavioral outcomes due to PAE in animal models ( Pascual et al, 2017 , Raineki et al, 2017 , Sanchez et al, 2017 , Noor et al, 2020 ), and to adverse neurodevelopmental outcomes in children with FASD ( Bodnar et al, 2020 ). Moreover, they suggest either genetic sex and/or endocrine environment modify the relationship between immune system, metabolism and behavior as has been documented in other preclinical studies ( Yao and Gregoire Nyomba, 2007 , Bodnar et al, 2016 , Nguyen et al, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, sex differences in PAE-linked cytokine expression, and the suppression of splenic Tregs, may elevate the risk for autoimmune disorders and explain variations in FASD-associated behaviors. These data are consistent with a number of previous studies that link immune system dysfunction to neuropathy and to adverse behavioral outcomes due to PAE in animal models ( Pascual et al, 2017 , Raineki et al, 2017 , Sanchez et al, 2017 , Noor et al, 2020 ), and to adverse neurodevelopmental outcomes in children with FASD ( Bodnar et al, 2020 ). Moreover, they suggest either genetic sex and/or endocrine environment modify the relationship between immune system, metabolism and behavior as has been documented in other preclinical studies ( Yao and Gregoire Nyomba, 2007 , Bodnar et al, 2016 , Nguyen et al, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
“…We, along with others, have previously reported that alcohol-consuming women with FASD children selected from the same parent cohort have a higher ratio of proinflammatory to anti-inflammatory cytokines compared to alcohol-consuming women with normally developing children (27,39,40). Specifically, an increase in third trimester tumor necrosis factor-a (TNF-a) relative to interleukin (IL)À10 was associated with increased risk of FASD in alcohol-consuming women (27).…”
Section: Discussionmentioning
confidence: 88%
“…The social communication problem as the core diagnostic feature in ASD children has been extensively studied in the field. However, the non-diagnostic features in ASD children have attracted great attention over the past decade; these include gastrointestinal problem 7 , sleep disorders 8 , immune system aberration 9 , neurotrophic factor dysregulation 10 , mitochondrial dysfunction 11 , and oxidative stress 12 . Oxidative stress may cause damages to lipids, proteins, and DNAs in cells, with subsequent disease development in humans 13 .…”
Section: Introductionmentioning
confidence: 99%